The role of Mungkus in Enhancing Creative Economic Resilience and Cultural Preservation through UMKM in Cikoneng - Ciamis - Adi Ramdani; Fakhir Elyanda Fadhlurrahman; Azka Irham Maulana; Saeful Millah (JAMASAN: Jurnal Mahasiswa Pendidikan Sejarah, 2026)
The study examines the role of Mungkus in enhancing creative economic resilience and cultural preservation through UMKM in Cikoneng District in the era of globalization. Using a qualitative approach with a case study method through interviews, observation, and documentation, the study identifies how Mungkus cultural values are integrated into the creative economic activities of UMKM, thereby strengthening competitiveness and preserving local culture. Creative economic resilience is measured using the Business Intelligence and Clustering (BIC) method, SWOT Analysis, Asset Based Community-Driven Development (ABCD), and Key Performance Indicators (KPI). The results show that Mungkus culture is a social capital, a strategic asset, and contributes significantly to the development of creative MSMEs that can strengthen the economic resilience of the community while preserving local cultural values and maintaining cultural identity amid the dynamics of globalization. The research recommends that local governments and stakeholders develop Mungkus culture-based MSME training and mentoring programs, expand market access, and encourage collaboration between cultural and creative economy actors to strengthen economic resilience and cultural preservation in Cikoneng District.